Horizontal and Vertical Movement Patterns and Habitat Use of Juvenile Porbeagles (Lamna nasus) in the Western North Atlantic - Skomal, Gregory; Marshall, Heather; Galuardi, Benjamin; Natanson, Lisa; Braun, Camrin D.; Bernal, Diego (Frontiers in Marine Science, 2021)
The porbeagle (Lamna nasus) is a large, highly migratory endothermic shark broadly distributed in the higher latitudes of the Atlantic, South Pacific, and Indian Oceans. In the North Atlantic, the porbeagle has a long history of fisheries exploitation and current assessments indicate that this stock is severely overfished. Although much is known of the life history of this species, there is little fisheries-independent information about habitat preferences and ecology. To examine migratory routes, vertical behavior, and environmental associations in the western North Atlantic, we deployed pop-up satellite archival transmitting tags on 20 porbeagles in late November, 2006. The sharks, ten males and ten females ranging from 128 to 154 cm fork length, were tagged and released from a commercial longline fishing vessel on the northwestern edge of Georges Bank, about 150 km east of Cape Cod, MA. The tags were programmed to release in March (n = 7), July (n = 7), and November (n = 6) of 2007, and 17 (85%) successfully reported. Based on known and derived geopositions, the porbeagles exhibited broad seasonally-dependent horizontal and vertical movements ranging from minimum linear distances of 937 to 3,310 km and from the surface to 1,300 m, respectively. All of the sharks remained in the western North Atlantic from the Gulf of Maine, the Scotian Shelf, on George's Bank, and in the deep, oceanic waters off the continental shelf along the edge of, and within, the Gulf Stream. In general, the population appears to be shelf-oriented during the summer and early fall with more expansive offshore radiation in the winter and spring. Although sharks moved through temperatures ranging from 2 to 26°C, the bulk of their time (97%) was spent in 6-20°C. In the summer months, most of the sharks were associated with the continental shelf moving between the surface and the bottom and remaining < 200 m deep. In the late fall and winter months, the porbeagles moved into pelagic habitat and exhibited two behavioral patterns linked with the thermal features of the Gulf Stream: “non-divers” (n = 7) largely remained at epipelagic depths and “divers” (n = 10) made frequent dives into and remained at mesopelagic depths (200–1000 m). These data demonstrate that juvenile porbeagles are physiologically capable of exploiting the cool temperate waters of the western North Atlantic as well as the mesopelagic depths of the Gulf Stream, possibly allowing exploitation of prey not available to other predators.